A review on high-strength engineered cementitious composites (HS-ECC): Design, mechanical property and structural application. (January 2022) - Ding, Yao; Yu, Kequan; Li, Mi
Abstract: The rapid development of infrastructure imposes high requirements on the performances of building materials especially on strength and ductility. The combination of high tensile strain capacity (>2%) and high strength (>80 MPa) to produce high strength engineered cementitious composites (HS-ECC) can be regarded as a potential and competitive option for structural application. The present paper comprehensively reviews some of the most important properties of HS-ECC from material scale to structural scale, and highlights several potential future research suggestions. The design theory of HS-ECC is firstly introduced, and the static and dynamic properties, size effect, energy properties, and shrinkage cracking resistance of HS-ECC are paid special attention to. Besides, the bond behavior between steel bar and HS-ECC matrix which is the fundamental for steel reinforced HS-ECC structure application is introduced, followed by the critical applications of HS-ECC in repairing the existed or advancing the newly-constructed infrastructures. Moreover, the possibility to partially or totally replace the binder materials or fibers in HS-ECC by recycle materials or industrial by-products is summarized, providing a greener solution. The future research directions of HS-ECC are also suggested to improve its property and enlarge its application area.